Cointegration in the Oil Market Among Regional Blends - Wilmot, Neil A. (International Journal of Energy Economics and Policy, 2013)
The integration of crude oil spot prices, from different geographic regions is examined using the residual-based cointegration test of Gregory and Hansen (1996), which allows for endogenously determined structural breaks. While traditionally, the focus has been on three global benchmark crudes (WTI, Brent and Dubai Fateh), herein the relationship among secondary, regional blends (Edmonton Par, Western Canadian Select, Bonny Light and Mexican Maya) is examined with implications for the ‘global pool’ hypothesis. Monthly data is examined, with particular emphasis placed on the Canadian perspective. The results indicate that the regional crudes, of similar and differing grades, are cointegrated with a structural break. Events with a direct impact on the crude market are linked to the structural breaks. Indirect impacts are attributed to events which appear to have affected crude oil prices via a decrease in demand, such as the economic uncertainty leading to and during the ‘Great Recession’. Keywords: Spot prices; cointegration; structural breaks JEL Classifications: C22; Q4